2024
DOI: 10.1007/s12094-023-03364-6
|View full text |Cite
|
Sign up to set email alerts
|

Senescence in head and neck squamous cell carcinoma: relationship between senescence-associated secretory phenotype (SASP) mRNA expression level and clinicopathological features

Kamila Ostrowska,
Patryk Niewinski,
Igor Piotrowski
et al.

Abstract: Background Cellular senescence is a state characterized by cell-cycle arrest and apoptotic resistance. Senescence in cancer may be induced by oncogenes or therapy. While cellular senescence might play an important role in protection against cancer development, elevated and uncontrolled senescent cells accumulation may promote carcinogenesis by secreting a collection of pro-inflammatory factors, collectively termed the senescence-associated secretory phenotype (SASP). Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…119 Moreover, prevalence of SASP factors such as CXCL1 was identified as a clinicopathological feature in patients with head and neck squamous cell carcinoma as compared to normal tissue. 120 Considering that cellular senescence and SASP are strongly associated with inflamm-aging and disease pathogenesis, limited yet emerging studies indicate that suppression of SASP or delaying cellular senescence might be sufficient to curb inflamm-aging and improve inflammatory homeostasis with age (Figure 3). We recently observed that long-term administration of major green tea catechin, i.e., epigallocatechin gallate (EGCG) in mice suppressed cellular senescence and SASP in animal tissues and also alleviated systemic markers of inflamm-aging, ultimately resulting in enhanced lifespan and healthspan.…”
Section: Cellular Senescence Augments Inflamm-agingmentioning
confidence: 99%
“…119 Moreover, prevalence of SASP factors such as CXCL1 was identified as a clinicopathological feature in patients with head and neck squamous cell carcinoma as compared to normal tissue. 120 Considering that cellular senescence and SASP are strongly associated with inflamm-aging and disease pathogenesis, limited yet emerging studies indicate that suppression of SASP or delaying cellular senescence might be sufficient to curb inflamm-aging and improve inflammatory homeostasis with age (Figure 3). We recently observed that long-term administration of major green tea catechin, i.e., epigallocatechin gallate (EGCG) in mice suppressed cellular senescence and SASP in animal tissues and also alleviated systemic markers of inflamm-aging, ultimately resulting in enhanced lifespan and healthspan.…”
Section: Cellular Senescence Augments Inflamm-agingmentioning
confidence: 99%